ANALISIS KESESUAIAN PERAIRAN UNTUK BUDIDAYA IKAN KERAPU BEBEK (Cromileptes altivelis) DI PERAIRAN PULAU TEGAL TELUK LAMPUNG - Desti Rizki Anggraini; Abdullah Aman Damai; Qadar Hasani (University of Lampung, 2018)
Tegal Island is part of Lampung Bay which has potential to be the location of aquaculture. One of kind fish that can be cultivated in these area is the humpback grouper (Cromileptes altivelis). Humpback grouper is the most popular fish species in local and foreign markets that have the highest selling price. The purpose of this study were to know the physical and chemical parameters in Tegal Island waters, to know the suitability of the waters for the humpback grouper cultivation in the waters of Tegal Island. The research was conducted in May 2017. The sampling location was 4 stations. The range of water quality values in Tegal island were water depth (15-25 m), dissolved oxygen (7 – 8 mg/l), brightness (5-10 m), salinity (30-34 ppt), temperature (28 – 32°C ), current velocity (20 – 50 m/s), pH (7,7 – 8,0), nitrate (0,9 – 3,2 mg/l) and phosphate (0,2 – 0,5 mg/l). The results showed that the waters of Tegal Island had appropriate water suitability level (St 3), corresponding marginally (St 1 and St 2) and unsuited (St 4) for the cultivation of humpback grouper.